Dose Dependent Anti-inflammatory Effect of Ammi majus Alcoholic Extract in Rat: Chronic Study - Shihab H. Mutlag (College of Pharmacy University of Baghdad, 2017)
During treatment of inflammatory diseases, many conventional therapies (non-steroidal anti-inflammatory drugs) used to relief pain and inflammation. Chronic use of  the intended drugs is frequently associated with serious side effect, which may lead to discontinuation of treatment . The efficacy and dose- response effect of ammi majus extraxt  (2 , 4, 8 , 16, and 32 mg/rat) were assessed using  formalin to induce paw edema in rats as a model of chronic inflammation respectively. In this study,  42 rats were used and allocated into 7  groups each containing 6 rats, representing control (Distilled  water) , standard (piroxicam ) and test extract ( 2 , 4 , 8 , 16 and 32 mg/rat of Ammi majus alcoholic extract ). The test extract and control were given orally before induction of inflammation Paw edema was measured by using vernier caliper after  7 days for chronic inflammation. The result indicated that Ammi majus alcoholic  extract significantly lower paw edema (p<0.05) compared to standard and control, while  the dose 16mg/rat also lower the paw edema compared with other test groups but less compared with the dose 32mg/rat. In conclusion, Ammi majus alcoholic extract possess anti-inflammatory activity in animals model of chronic inflammation and the effect increased with increasing the dose. Key words: Ammi majus  alcoholic extract, Chronic inflammation , Dose-Dependent .